Eect of dierent types of substrate, in the production of Lilium bulbils (Lilium Sp) from scales, in the district of Independencia-province of Huaraz- department of Ancash - Olinda Mallqui, Evita (2019)
Experimental work was carried out, with the objective of evaluating four types of substrates, in the production of bulbils from Lilium scales (Lilium sp). The Completely Random Design (DCA) was used, with 4 treatments and 3 repetitions. The treatments were T1 (1 Sand: 1 Peat), T2 (1 Sand: 1 Compost), T3 (1 Sand: 1 Humus) and T4 (1 Sand: 1 Sawdust). The evaluation parameters were: number of bulbils, diameter of bulbils (cm),weight of bulbils (gr.), Length of roots (cm) and number of roots. The substrate in proportions of 1 Sand: 1 Sawdust (Treatment T4), was the most optimal for the production of lilium bulbils (Lilium sp), from scales, having obtained 2 bulbils per scale, 0, 93 cmin diameter per bulbil, 0, 588gr of weight per bulbil, 4, 9 cmlength of root per bulbil and 4 roots per bulbillo; Perú